MUHAMMAD BIN ABDUL WAHAB: GERAKAN REVIVALISME DAN PENGARUHNYA - Nurlaelah Abbas (Fakultas Dakwah dan Komunikasi, 2015)
In order to respond to the challenges of the modern world, it is key to preserving Islam as the religion of those perfect and universal, is through increasing the public's understanding of religion. Movement of renewal and purification, back to the Qur'an and Sunnah, therefore aims at translating the spirit of the teachings of Islam contained in these two sources. Muhammad bin Abdul Wahab may be classed as productive scholars. It can be seen from the number of books he authored the tens titles. The birth of ideology Wahabiah by Muhammad ibn Abd Wahab, not in spite of the pros and cons. The group that pro rate it is a prudent undergo particular religious worship (devotion) to God as the goal of life. Semetrara cons, assessing it as a matter of extreme because many things related to social, neglected for consideration heretical and idolatrous.